Ideas for the animated short : finding and building stories. - Sullivan, Karen, 1964-; Alexander, Kate, ....-; Schumer, Gary, ....- (Amsterdam : Elsevier, 2008)
Why read this book; Telling Stories; Where do Ideas Come From?; Building Stories; Building characters and Locations; The purpose of dialogue; Acting; Staging; Storyboarding; Animatics; Case Studies; Glossary
Keywords: Scenario's.